As cotas nas universidades públicas brasileiras - Martini, Andressa Ferreira de (2009)
This work aims to gather data concerning the implementation of the quota system in universities to learn how institutions have handled this process. We believe that higher education has been a prime area of debate in Brazil as a place to think the discussions, issues and assumptions made about this proposal of affirmative action. The specialized bibliography have done us understand the importance of the North American reference in Brazil on this subject. Therefore, constitute the historical context of affirmatives actions in the U.S. through the movement of the struggle for racial equality that demanded the expansion of the rights of black citizens. We could note in the national context, the implementation of quotes revels that define the reservation of vacancies only is not enough, because the accumulating challenges when starting to operate, since the social reach inherent to it in much beyond the university and its links with other levels of the educational system. There are crucial social and political processes for the construction of the national project in progress and the question of abolition of racial inequalities emerge as a central element in that direction